Role of Abdullah Ahmad on the Modernization of Islamic Education in Minangkabau - Rafles, H.; Taufan, Muhammad; Sabiruddin, Sabiruddin (Islamic Studies and Development Center (ISDC) Universitas Negeri Padang, 2017)
The objective of this study is to explore the role of Abdullah Ahmad on the development of Islamic education in Minangkabau. The research used qualitative method with individual life history approach. All data was collected through a biography of the character, literatures, documents and evidence of object legacy in terms of both written and physical data. Data collection was conducted through the process of collecting, reducting, and presenting the data and was followed by a conclusion. Overall, the result of the study shows that there are six methods applied by Abdullah Ahmad in developing the Islamic education in Minangkabau. The six methods are: i) religion-based education, ii) integration of classical and modern educational models, iii) educational consortium, iv) development of a scientific culture, v) receptiveness to modernization, and vi) informal education. This study also proves that the Abdullah Ahmad’s six methods of education are the prototype of the establishment of today’s various modern educational institutions in West Sumatra. It is no wonder that Minangkabau was formerly known as the land for producing Islamic scholars, intellectuals and powerful politicians such as M. Yamin, Buya Hamka, M. Nasir, and Muhammad Hatta. Based on the historical facts, this study found that Minangkabau scholars, intellectuals and politicians are influenced more or less by the thoughts of Abdullah Ahmad.